FORMATION OF IDEAS ABOUT MICROMECHANICS DESTRUCTION IN THE PROCESS OF TEACHING A PHYSICS COURSE - Bozorov Nosirjon Sodikovich Umurkulov Kayumjon Parpievich, Alisherov Otabek Alisher ugli; Abdumanonova Firuza Abdualievna (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the role of microcracks in fractures and evaluates the strength of solids in the framework of continuum mechanics concepts. It is shown that although the assessment of the role of microcracks in the fracture and strength of solids proposed by Griffiths was an important step, this approach does not take into account the dynamic role of the occurrence of microcracks and the relaxation nature of the absorption of the released elastic deformation energy. The involvement of the concepts and achievements of micromechanics of destruction in teaching the relevant topics of the course of physics makes it possible to acquaint pupils and students with the real problems of modern science and thereby increase the efficiency of the educational process.